Pengaruh Nisbah Dan Suhu Pencampuran Terhadap Sifat Campuran Aspal – Crumb Rubber - Desi Purnama Sari; Irdoni Irdoni; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Modified asphalt is one of the alternative to method the road problems in Indonesia. This experiment aims to determine the effect of mixing ratio and temperature towards the property of asphalt - crumb rubber. This research method conducted by varied ratio 5%, 8% and 10% of melted crumb rubber. Then, mixsed with melt asphalt. The temperature variation of this process were at 150 oC and 170 oC for 60 minutes. The softening point, penetration, marshall stability and loss weight were tested from the modified asphalt. The results of this study indicated that the modified asphalt with crumb rubber has increased the value of softening point, penetration, stability marshall and decrease the loss weight. The best results was at 150 oC with 10% of crumb rubber, which has the softening point at 52 oC, penetration at 74.1 mm, marshal stability 1266.7 kg and loss weight 0.017%.Keywords : asphalt modified, crumb rubber, mixing ratio, penetration, stability marshall